The Pacific Alliance: Fiction in Government Communication - Olivera-Cárdenas, Luis (2017)
We focus on the Pacific Alliance by developing an interdisciplinary approach between political communication and international relations. Four government entities broadcast messages on social media about this intergovernmental international agency. 236 analyzed messages lead to identify how the Government deals with the reality and potential of the Pacific Alliance. It is a political communication deprived of “myth”, which does not contribute to build consensus; likewise, it is a matter of presence in the Pacific Alliance that underperforms its potential to foster a proactive international policy.